IMPLEMENTASI KEBIJAKAN E-GOVERNMENT DI DINAS PENDIDIKAN KOTA SEMARANG DALAM LAYANAN PENDIDIKAN DASAR - Sodikin, Fauzan Abdullah; Subowo, Ari; Suwitri, Sri (Journal of Public Policy and Management Review, 2024)
This research examines how the implementation of e-government policies carried out by the Semarang City Education Office. This research was conducted using a qualitative descriptive method, by collecting data through interviews and direct observation both at the Semarang City Education Office and on social media used by officers to disseminate public information. The results obtained are the factors related to policy implementation, namely Communication Factors, Resources, Disposition and Bureaucratic Structure, only there are obstacles in the resource factor, namely the lack of PPID staff who are implementers of the policy, apart from that the supporting facilities have not been fulfilled . Even though the number of staff is inadequate, implementers have expertise in implementing these policies, namely being able to operate websites and social media as a means of disseminating public information. This is one of the supports for the successful implementation of the policies carried out.